PERAN PENDIDIKAN POLITIK DALAM MENINGKATKAN LITERASI POLITIK MAHASISWA DI ERA MEDIA DIGITAL - Rafli; Tetep (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Political education plays an important role in shaping students’ political literacy, particularly amid the increasingly massive development of digital media. Digital media not only serves as a source of political information but also influences students’ ways of thinking, attitudes, and political participation. This study aims to analyze the role of political education in enhancing students’ political literacy in the digital media era as well as its implications for political attitudes and participation. This research employs a qualitative approach using a literature review method by collecting data from various scholarly articles, books, and relevant academic sources. The findings indicate that political education contributes significantly to improving students’ understanding of political systems, democratic values, and critical thinking skills in responding to political information in digital media. Furthermore, adequate political literacy encourages the formation of rational, responsible, and participatory political attitudes. Therefore, strengthening political education that is adaptive to digital media developments is a strategic necessity in building a politically literate young generation committed to democratic values.